Pharmacokinetics of Sustained-release, Oral, and Subcutaneous Meloxicam over 72 Hours in Male Beagle Dogs - Smith, Brian J (J Am Assoc Lab Anim Sci, 2020)
In cynomolgus macaques, plasma levels of sustained-release formulations of meloxicam meet or exceed efficacious concentrations for 48 to 72 h, thereby allowing less animal handling and providing more consistent efficacy than standard formulations of meloxicam. The goal of this study was to compare the pharmacokinetics of a single subcutaneous dose of a sustained-release formulation of meloxicam (Melox-SR) with those of oral (Melox-PO) and standard subcutaneous (Melox-SC) formulations dosed every 24 h for 3 consecutive days. Dogs (5 or 6 adult male Beagles) each received the following 3 treatments: first, Melox-SR (10 mg/mL, 0.6 mg/kg SC once), next Melox-SC (0.2 mg/kg SC once, followed by 0.1 mg/kg SC every 24 h), and finally Melox-PO (same dosage as Melox-SC), with a washout period of at least 2 wk between formulations. Blood was collected at 0 (baseline), 1, 4, 8, 12, 24, 48, and 72 h after the initial administration of each formulation for comparison of meloxicam plasma concentrations. Blood was also collected before administration and at 48 h after Melox-SR injection for CBC and chemistry analysis. Plasma concentrations (mean ± 1 SD) of Melox-SR peaked at the 1-h time point (2180 ± 359 ng/mL), whereas those of Melox-PO (295 ± 55 ng/mL) and Melox-SC (551 ± 112 ng/mL) peaked at the 4-h time point. Melox-SR yielded significantly higher plasma concentrations than Melox-PO and Melox-SC until the 48 and 72-h time points, respectively. Melox-SC plasma concentrations were significantly higher than those of Melox-PO at 4, 8, 12, 24, 48 and 72 h. No lesions were noted at the Melox-SR injection sites, and Melox-SR administration was not associated with changes in the CBC and serum chemistry panels. A single 0.6-mg/kg dose of Melox-SR can yield plasma concentrations that exceed 350 ng/mL for at least 72 h in adult male dogs.